Application of linear programming to optimize profit of SME products / Ahmad Husaini Mohd Azahar, Nur Dayana Adam and Siti Aisyah Abdullah - Mohd Azahar, Ahmad Husaini; Adam, Nur Dayana; Abdullah, Siti Aisyah (2022)
Planning in production is frequently challenging for small and medium-sized enterprises (SMEs). Most SMEs struggle to determine the optimal level of production output, which can have a negative impact on their business's performance. Numerous businesses have utilized linear programming models to determine the optimal combination of various products to produce to maximize profits. Thus, this study aims to maximize the profits of an SME company in Malaysia using a linear programming model as well as to optimize the production planning of a company by using the linear programming method that will suggest a viable product mix to ensure optimal profit for the company. One of the SME companies in Malaysia was selected as the case study company for this study. Various conclusive observations and recommendations have been made. This study benefits the exposure of Malaysian SME owners to linear programming methods in decision making to determine maximum profitability for different product mixes. In addition, this study also benefits the field of mathematics because linear programming helps in converting verbal descriptions & numerical data into mathematical expressions and helps in achieving optimal productive use of resources.